We are the Process: Reflections on the Underestimation of Power in Students as Partners in Practice - Kehler, Angela; Verwoord, Roselynn; Smith, Heather (International Journal for Students as Partners, 2017)
The concept of Students as Partners (SaP) has much merit; however, further reflection on the power embedded in daily SaP processes and relationships is needed. In this article, we use the SaP model articulated by Healey, Flint, and Harrington (2014) to examine three reflections of SaP in practice from two different Canadian post-secondary contexts. Informed by critical pedagogical theory and feminist theory, we highlight sites of harmony and dissonance between the Healey, Flint, and Harrington (2014) model (theory) and our reflections (practice) and highlight embedded power relations in SaP processes and practices. We argue that there is often an underestimation of power in SaP.